Tailored Cu active sites in 2D MOF-derived carbon nanosheets for dual electrochemical detection of chloramphenicol and paracetamol - Zhi-Lun Wu; Tsai-Ting Liu; Mei-Hong Tang; Sheng-Fei Lin; Yu-Jen Shih (Chemical Engineering Journal, 2026)

Dynamic electronic and spin-state modulations of ternary single-atom catalysts for ultrahigh power density and ultra-stable rechargeable zinc-air batteries - Yu-Chieh Ting; Shao-I Chang; Kai-An Lee; Chiung-Wen Chang; Tzu-Hsiang Lin; Chih-Heng Lee; Hsin-Yi Tiffany Chen; Shih-Yuan Lu (Chemical Engineering Journal, 2026)

Formaldehyde activates the RUNX1–ISX axis to promote leukemic reprogramming, a pathway associated with poor prognosis in pediatric B-ALL - Pei-Chin Lin; Li-Ting Wang; Li-Heng Ye; Pin-Ying Tseng; Pei-Hsien Huang; Wan-Yi Hsu; Yu-Mei Liao; Shyh-Shin Chiou; Shih-Hsien Hsu (Environmental Pollution, 2026)

Effective metal recovery from lithium-ion battery waste using a ternary deep eutectic solvent in a high solid-to-liquid ratio under mild and ambient conditions - Hsin-Jou Cheng; Yi-Jane Lin; Shu-Chi Chang; Shih-Yen Yang; Ting-Wei Lee; Chiaying Chen (Journal of Environmental Chemical Engineering, 2026)

Chlorine-resistant high-entropy spinel oxide catalyst for efficient and durable seawater anion exchange membrane water electrolysis - Thi Xuyen Nguyen; Ting-You Shih; Ngoc Thanh Thuy Tran; Thanh Tuan Nguyen; Yi-Chuan Chu; Bo-Han Lai; Chun-Kuo Peng; Yu-Ru Lin; Yan-Gu Lin; Kao-Shu Chuang; Jeng-Kuei Chang; Thi Y Phung Nguyen; et al. (Chemical Engineering Journal, 2026)

Carbon footprint assessment of Taiwan's aquaculture industry integrated with solar photovoltaics: A comprehensive review - Hsin-Yi Liu; Asif Ali Bhat; Yu-Wei Chen; Shin-Yu Chen; Ming-Kuei Shih; Kuo-Huan Ting; Chia-Hua Lin; Chih-Yao Hou (Aquaculture, 2026)

Improvement of indoor air quality and health effects in COPD patients in a heavy industrial area - Jia Lin Zhang; Yi Ting Chang; Ching Yu Hsiao; Chung-Shin Yuan; Yen-Ping Peng; Da Wei Wu; Huang-Chi Chen; Jia-Yu Kuo; Huai-Lei Juan; Pei-Shih Chen (Environmental Research, 2026)

The O-acetylation on phage tail-spike protein digested penta-saccharide from Acinetobacter baumannii SK44 plays a critical role in triggering pro-inflammatory immune response - Tzu-Yin Huang; Yen-Ju Yang; Boh-Woon Tay; Chun-Ting Lin; Shih-Hsiung Wu; I-Ming Lee (Carbohydrate Polymers, 2026)

Correction: Dapagliflozin protects against doxorubicin-induced cardiotoxicity by restoring STAT3 - Wei-Ting Chang; Jhih-Yuan Shih; Yu-Wen Lin; Zhih-Cherng Chen; Wei-Chih Kan; Tsung-Hsien Lin; Chon-Seng Hong (Archives of Toxicology, 2026)

Isomeric halide engineering of self-assembled hole-selective layers for efficient indoor perovskite photovoltaics - Zhong-En Shi; Yi-Ting Hong; Cheng-Chieh Lu; Po-Cheng Shih; Shih-I Lu; Hsiao-Chi Hsieh; Sie-Rong Li; Yu-Che Lin; Zheng-Xuan Cai; Yan-Duo Lin; Chih-Ping Chen (Chemical Engineering Journal, 2026)

Correction: Severe enterovirus A71 pathogenesis and immune responses in human nucleolin transgenic mice - Nien-En Hsiao; Ya-Fang Wang; Yi-Chen Lin; Wei-Ting Chou; Li-Jin Hsu; Shih-Min Wang; Jen-Ren Wang; Ming-Derg Lai; Shun-Hua Chen; Chuan-Fa Chang (Medical Microbiology and Immunology, 2025)

Severe enterovirus A71 pathogenesis and immune responses in human nucleolin transgenic mice - Nien-En Hsiao; Ya-Fang Wang; Yi-Chen Lin; Wei-Ting Chou; Li-Jin Hsu; Shih-Min Wang; Jen-Ren Wang; Ming-Derg Lai; Shun-Hua Chen; Chuan-Fa Chang (Medical Microbiology and Immunology, 2025)

Light-capture capability based flexible negative pyramid microarrays coated with silver nano-islands for SERS detection - Chia-Hsien Lin; Yun-Chu Chen; Kuan-Syun Wang; Ding-Jia Yueh; Shih-Hsien Yeh; Jeng-Shiung Chen; Yung-Hsin Cheng; Yuh-Lin Wang; Ting-Yu Liu (Chemical Engineering Journal, 2025)

Synergistic enhancement of PBAT biodegradation by Purpureocillium lilacinum BA1S: Insights from transcriptomics and functional analyses - Wei-Sung Tseng; Min-Jia Lee; Tzu-Yen Chen; Shih-Shun Lin; Sheng-Lung Chang; Pei-Yin Lin; Ting-Jang Lu; Chi-Te Liu (Journal of Hazardous Materials, 2025)

Polycyclic aromatic hydrocarbon aggravates high-fat diet-induced metabolic dysfunction-associated steatotic liver disease through disturbing hepatocyte sphingolipid metabolism - Hui-Ru Kuo; Yu-Fen Chung; Li-Ting Wang; Chih-Wen Wang; Shih-Hsien Hsu; Li-Chen Chen; Ming-Hong Lin; Shau-Ku Huang; Kwei-Yan Liu (Environmental Pollution, 2025)

Humidity-dependent ammonium formation and enhanced light scattering in agricultural aerosols - Chien-Hao Lin; Ling-Ya Chen; Ting-Yu Chiang; Sally C. W. Tai; Shih-Yu Chang (Environmental Geochemistry and Health, 2025)

Synergistic modulation of electronic structure in high entropy perovskite oxide for enhanced bifuntional oxygen evolution/reduction reactions and its mechanistic insights via in-situ analyses and density functional theory calculation - Thi Xuyen Nguyen; Chih-Heng Lee; Jun-Hong Sun; Chun-Kuo Peng; Wen-Hui Chu; Hamed Pourzolfaghar; Yu-Ru Lin; Muhammad Ghufron; Yuan-Yao Li; Yu-Hao Chang; Yan-Gu Lin; Hsin-Yi Tiffany Chen; et al. (Chemical Engineering Journal, 2025)

Advances and Challenges of Tissue Vascular Scaffolds and Supercritical Carbon Dioxide Technology in Cardiovascular Diseases - Horng-Ta Tseng; Yi-Wen Lin; Shih-Ying Sung; Yi-Ting Tsai; Chen-Wei Liu; Po-Shun Hsu; Chien-Sung Tsai; Feng-Yen Lin (Tissue Engineering and Regenerative Medicine, 2025)

Investigating the Sensitivity of NIPAM Gel Dosimetry in CyberKnife Systems Using MRI-based R2 Mapping - Yu-Hsuan Lin; Shih-Wei Huang; Hung-Yi Chen; Hao-Ting Lan; Feng-Yi Su; Shin-Lei Peng; Chun-Hsu Yao (Journal of Medical and Biological Engineering, 2025)
Purpose The CyberKnife delivers precise radiation with sharp dose gradients challenging to measure. N-isopropylacrylamide (NIPAM) gel phantom can capture 3D dose distributions effectively. This study investigates the feasibility of using NIPAM gel dosimetry combined with magnetic resonance imaging (MRI)-based transverse relaxation rate (R2) mapping to verify dose distributions delivered by the CyberKnife system. Methods A total of 24 gel samples were divided into 8 dose groups (0, 3, 6, 9, 12, 15, 18, and 21 Gy), with three samples per dose group for repeat measurements. The NIPAM polymer gels were irradiated by a CyberKnife ® M6 FIM system with a 6 MV x-ray beam. MR images of the NIPAM gel phantom were made 24 h after irradiation using the 3T MRI scanner. The R2 maps corresponding to dose distribution were analyzed using Matlab software. Results Our results demonstrate that R2 values increase with rising irradiation doses, confirming dose-dependent sensitivity. The dose-response curve exhibits a slope of 0.1688 Gy⁻¹ s⁻¹, reflecting the gel dosimeter’s sensitivity, with a strong correlation (R² = 0.85, p = 0.001). Additionally, R2 values vary with depth, peaking at the 30 mm dose center point (D center ) and then gradually decreasing, indicating maximum dose accumulation at D center followed by a decline with increasing depth. Conclusion This study demonstrates that NIPAM gel dosimetry with MRI-based R2 mapping effectively verifies CyberKnife dose distributions. It exhibits strong dose sensitivity and accurately captures sharp gradients, highlighting its potential as a superior alternative to conventional dosimetry methods.

What does it mean when the pleasant smells come and go? Correlation between UPSIT odor identification status and fluctuation of non-motor symptoms in Parkinson’s disease - Hsin-Bei Lei; Ting-Chun Fang; Yu-Hsuan Lin; Shih-Chi Chiu; Ming-Hong Chang; Yi-Jen Guo (Acta Neurologica Belgica, 2025)
Parkinson’s disease (PD) is characterized by motor and non-motor symptoms, including olfactory dysfunction. Prior studies have shown that olfaction deteriorates with disease progression, however fluctuations in olfaction and related PD symptoms have been less explored. This study aimed to investigate correlations between changes in odor identification ability and PD symptoms. PD patients recruited from Taichung Veterans General Hospital underwent at least two consecutive Movement Disorder Society Unified Parkinson’s Disease Rating Scale (MDS-UPDRS) and University of Pennsylvania Smell Identification Test (UPSIT) evaluations. The patients were grouped based on changes in olfactory identification ability between evaluations, and fluctuations in PD symptoms were compared between groups. Ninety-seven PD patients with 114 complete sets of data were analyzed. Significant divergent results were observed between changes in five MDS-UPDRS non-motor subscores and the conversion status of five pleasant odors, including anxiety vs. bubble gum, apathy vs. banana, dizziness vs. coconut, urination vs. root beer, and dopamine dysregulation syndrome (DDS) vs. grape. Fluctuations in the ability to detect pleasant odors, may have a complex interaction with other non-motor symptoms, including in the neurobehavioral and autonomic domains. Serial monitoring of olfactory function, particularly with pleasant odors, may provide valuable insights for tracking non-motor symptoms in PD and warrants further investigation into their therapeutic implications.

Safety evaluation of Limosilactobacillus fermentum PS150 for use as a commercial psychobiotic - Li-Hao Cheng; Chien-Chen Wu; Chin-Lin Huang; Yu-Hsuan Wei; Pei-Jun Wen; Shih-Hau Chiu; Chien-Chi Chen; Ching-Ting Lin; Po-Lin Liao (Food and Chemical Toxicology, 2025)

Methane Index and TEX86 values in cold seep sediments: Implications for paleo-environmental reconstructions - Sze Ling Ho; Yu-Shih Lin; Pei-Ling Wang; Tzu-Ting Chen; Pei-Ting Lee; Hui-Hsin Wang; Tzu-Jung Cheng; Yun-Ju Wang; Chih-Chieh Su; Min-Te Chen (Geochimica et Cosmochimica Acta, 2025)

Sulfur-functionalized sawdust biochar for enhanced cadmium adsorption and environmental remediation: A multidisciplinary approach and density functional theory insights - M.M.M. Ahmed; Chih-Hao Liao; S. Venkatesan; Yu-Ting Liu; Yu-Min Tzou; Shih-Hao Jien; Ming-Chang Lin; Yi-Cheng Hsieh; Ahmed I. Osman (Journal of Environmental Management, 2025)

Sulfur-functionalized rice straw biochar for enhanced cadmium sorption: Spectroscopic, kinetic and computational insights - M.M.M. Ahmed; Chih-Hao Liao; Yu-Ting Liu; S. Venkatesan; Yi-Chen Hsieh; H.M. Nail; Hui-Min David Wang; Ming-Chang Lin; Shih-Hao Jien; Yu-min Tzou (Journal of Cleaner Production, 2024)

Streptococcus taoyuanensis sp. nov., a Novel Species Isolated from a Patient with Bacteremia - Chien-Yu Lee; Chin-Kan Chan; Yi-Sheng Chen; Yun-Shien Lee; Shih-Ting Lin; Yu-Chung Chang; Hui-Chung Wu; Jia-rong Zhang; Hong-yu Chen; Li-Ting Wang (Current Microbiology, 2024)

The impact of flooding from the Minjiang River on the succession of harmful algal blooms (HABs) caused by diatoms in China's offshore waters - Yun-Chi Lin; Ya-Han Nien; Kuo-Ping Chiang; Chien-Pang Chin; Wei-Ting Chen; Gwo-Ching Gong; Wen-Chen Chou; Chi-Yu Shih; Kuo-Shu Chen (Marine Pollution Bulletin, 2024)

The toxicity of chlorine dioxide to clownfish and its bactericidal capability to pathogenic strains of vibrio spp. - Chia‐Te Lin; Juan‐Ting Liu; Pei‐Chi Wang; Shih‐Chu Chen (Journal of Fish Diseases, 2024)
Global ornamental fish transportation ranging from hours to days can produce multiple stress factors impact fish health and cause mortality. Clownfish, particularly Amphiprion ocellaris , are among the most traded saltwater ornamental fish. Vibrio includes several pathogenic strains that affect aquatic animals. Consequently, prophylactic treatment of the water or fish is recommended. In this study, six Vibrio strains including V. alginolyticus , V. parahaemolyticus and V. harveyi isolated from sick A. ocellaris and one V. harveyi strain from a sick East Asian fourfinger threadfin ( Eleutheronema rhadinum ) were tested for their sensitivity to a popular disinfectant, chlorine dioxide (ClO 2 ). The results showed that 0.25 ppm ClO 2 effectively suppressed five of the seven tested Vibrio strains for 24 h; however, 0.1 ppm ClO 2 is safer for A. ocellaris . Meanwhile, ClO 2 2.5 ppm reduced the bacterial counts to below 3.3 × 10 5 CFU/mL for 24 hours. The LC 50 of ClO 2 for A. ocellaris was 0.87 ppm at 10 min and 0.72 ppm at 24 h post treatment. Mild changes in water quality, including dissolved oxygen (DO), temperature and pH, were recorded during the trial. More research is necessary to understand the sensitivity of various aquatic animal pathogens to ClO 2 and its toxicity to different aquatic animals.

Examining arterial pulsation to identify and risk-stratify heart failure subjects with deep neural network - Chieh-Chun Huang; Shih-Hsien Sung; Wei-Ting Wang; Yin-Yuan Su; Chi-Jung Huang; Tzu-Yu Chu; Shao-Yuan Chuang; Chern-En Chiang; Chen-Huan Chen; Chen-Ching Lin; Hao-Min Cheng (Physical and Engineering Sciences in Medicine, 2024)
Hemodynamic parameters derived from pulse wave analysis have been shown to predict long-term outcomes in patients with heart failure (HF). Here we aimed to develop a deep-learning based algorithm that incorporates pressure waveforms for the identification and risk stratification of patients with HF. The first study, with a case–control study design to address data imbalance issue, included 431 subjects with HF exhibiting typical symptoms and 1545 control participants with no history of HF (non-HF). Carotid pressure waveforms were obtained from all the participants using applanation tonometry. The HF score, representing the probability of HF, was derived from a one-dimensional deep neural network (DNN) model trained with characteristics of the normalized carotid pressure waveform. In the second study of HF patients, we constructed a Cox regression model with 83 candidate clinical variables along with the HF score to predict the risk of all-cause mortality along with rehospitalization. To identify subjects using the HF score, the sensitivity, specificity, accuracy, F1 score, and area under receiver operating characteristic curve were 0.867, 0.851, 0.874, 0.878, and 0.93, respectively, from the hold-out cross-validation of the DNN, which was better than other machine learning models, including logistic regression, support vector machine, and random forest. With a median follow-up of 5.8 years, the multivariable Cox model using the HF score and other clinical variables outperformed the other HF risk prediction models with concordance index of 0.71, in which only the HF score and five clinical variables were independent significant predictors (p < 0.05), including age, history of percutaneous coronary intervention, concentration of sodium in the emergency room, N -terminal pro-brain natriuretic peptide, and hemoglobin. Our study demonstrated the diagnostic and prognostic utility of arterial waveforms in subjects with HF using a DNN model. Pulse wave contains valuable information that can benefit the clinical care of patients with HF.

Non-precious bifunctional high entropy alloy catalyst and layered double hydroxide enhanced gel electrolyte based rechargeable flexible zinc-air batteries - Ting-Yu Lin; Fan-Yu Yen; Yu-Chieh Ting; Po-Wei Chen; Shih-Yuan Lu (Chemical Engineering Journal, 2024)

Extinction coefficient of dry and deliquescent chemical components of PM_(2.) 5 in urban areas and their impacts on visibility deterioration - Chien-Hao Lin; Shao-En Sun; Chung-Te Lee; Ting-Yu Chiang; Shih-Yu Chang; Tzu-Shuan Wu; Hsin-Yu Wei; Ling-Ya Chen; Hao-Wei Liu; Sally C.W. Tai (Atmospheric Pollution Research, 2024)

Impact of Pacific–Japan pattern on temperature and heatwave events in summer over Taiwan - Wan‐Ling Tseng; Szu‐Ying Lin; Yi‐Chi Wang; Shih‐How Lo; Min‐Hui Lo; Shih‐Yu Lee; Chieh‐Ting Tsai; Huang‐Hsiung Hsu (International Journal of Climatology, 2023)
The prediction of heatwave events is vital to provide information on possible hazards caused by extremely high temperature. The Pacific–Japan (PJ) pattern is a significant climate variability that controls the summer climate over East Asia. Previous studies have reported that the meridional propagating wave structure associated with the PJ pattern can modulate summer temperature and heatwave characteristics over northeast Asian countries, such as Korea and Japan. Nevertheless, its impacts on the subtropical regions, including Taiwan, a mountainous subtropical island with an approximate population of 24 million, is not yet fully understood. In this study, we investigate the impacts of the PJ pattern on the summer temperature and heatwave characteristics in Taiwan on the interannual timescale using long‐term station‐based temperature and rainfall dataset. We found an island‐wide increase in temperature during the positive phase of the PJ pattern, which is characterized by an anticyclonic anomalous circulation over Taiwan. Meanwhile, the averaged effective area and frequency of heatwave extremes over Taiwan have increased significantly, indicating an increase of exposure to heatwaves. Our examinations of large‐scale environment suggest that the adiabatic warming due to subsidence anomaly associated with the anticyclone over Taiwan is primary contributor of surface warming, which is balanced by diabatic cooling and meridional advective cooling on a seasonal timescale. Our study consolidated the links between the PJ pattern as a climate driver, hot summers and increased summer heatwave events over Taiwan. By combining with the seasonal prediction systems and early warning systems, such understanding can help sectors that are vulnerable to heat stress to prepare for potential hazards.

Remediation of diesel-oil contaminated soils using an innovative nanobubble and electrolyzed catalytic system - Wei-Ting Chen; Justin Chun-Te Lin; Shih-Hsiung Chen; Francis Verpoort; Kun-Liang Hong; Rao Y. Surampalli; Chih-Ming Kao (Journal of Cleaner Production, 2023)

Associations between paraben exposure, thyroid capacity, homeostasis and pituitary thyrotropic function in the general Taiwanese: Taiwan Environmental Survey for Toxicants (TEST) 2013 - Po-Chin Huang; Hsin-Chang Chen; Shih-Hao Leung; Yu-Jung Lin; Han-Bin Huang; Wan-Ting Chang; Hsin-I. Huang; Jung-Wei Chang (Environmental Science and Pollution Research, 2023)

Magnusiomyces Capitatus Lung Nodule in a Patient with Nasopharyngeal and Hepatocellular Carcinoma - Shih-Hao Lo; Hsin-Hui Wang; Ya-Ting Chang; Chih-Hung Lin; Po-Liang Lu; Shang-Yi Lin (Mycopathologia, 2023)

Estimating hydrogeological parameters at groundwater level observation wells without pumping well information - Hwa-Lung Yu; Shih-Yao Lee; Hua-Ting Tseng; Ying-Fan Lin (Journal of Hydrology, 2023)

Investigating the stretchability of doped poly(3-hexylthiophene)-block-poly(butyl acrylate) conjugated block copolymer thermoelectric thin films - Qing-Bao Zheng; Yan-Cheng Lin; Yen-Ting Lin; Yun Chang; Wei-Ni Wu; Jhih-Min Lin; Shih-Huang Tung; Wen-Chang Chen; Cheng-Liang Liu (Chemical Engineering Journal, 2023)

Applying expanded metal mesh for outdoor shades in outdoor thermal environments - Shing-Ru Yang; Shih-Tang Lan; Yi-Ting Wu; Tsuyoshi Honjo; Tzu-Ping Lin (International Journal of Biometeorology, 2023)

Cadmium exposure induces histological damage and cytotoxicity in the cardiovascular system of mice - Shing-Hsien Chou; Hung-Chen Lin; Shao-Wei Chen; Yu-Ting Tai; Shih-Ming Jung; Fu-Hsiang Ko; Jong-Hwei Su Pang; Pao-Hsien Chu (Food and Chemical Toxicology, 2023)

Genomic architecture underlying morphological and physiological adaptation to high elevation in a songbird - Chia‐Wei Lu; Shih‐Ting Huang; Shun‐Jen Cheng; Chen‐Tau Lin; Yu‐Cheng Hsu; Cheng‐Te Yao; Feng Dong; Chih‐Ming Hung; Hao‐Chih Kuo (Molecular Ecology, 2023)
Organisms often acquire physiological and morphological modifications to conquer ecological challenges when colonizing new environments which lead to their adaptive evolution. However, deciphering the genomic mechanism of ecological adaptation is difficult because ecological environments are often too complex for straightforward interpretation. Thus, we examined the adaptation of a widespread songbird—the rufous‐capped babbler ( Cyanoderma ruficeps )—to a relatively simple system: distinct environments across elevational gradients on the mountainous island of Taiwan. We focused on the genomic sequences of 43 birds from five populations to show that the Taiwan group split from its sister group in mainland China around 1–2 million years ago (Ma) and colonized the montane habitats of Taiwan at least twice around 0.03–0.22 Ma. The montane and lowland Taiwan populations diverged with gene flow between them, suggesting strong selection associated with different elevations. We found that the montane babblers had smaller beaks than the lowland ones, consistent with Allen's rule, and identified candidate genes— COL9A1 and SOX11 —underlying the beak size changes. We also found that altitudinally divergent mutations were mostly located in noncoding regions and tended to accumulate in chromosomal inversions and autosomes. The altitudinally divergent mutations might regulate genes related to haematopoietic, metabolic, immune, auditory and vision functions, as well as cerebrum morphology and plumage development. The results reveal the genomic bases of morphological and physiological adaptation in this species to the low temperature, hypoxia and high UV light environment at high elevation. These findings improve our understanding of how ecological adaptation drives population divergence from the perspective of genomic architecture.

Evaluation of a subtropical maize-rice rotation system maintained under long-term fertilizer inputs for sustainable intensification of agriculture - Asif Hameed; Yu-Pei Chen; Fo-Ting Shen; Shih-Yao Lin; Hsin-I Huang; Yu-Wen Lin; Chiu-Chung Young (Applied Soil Ecology, 2023)

Modeling of an integrated H2S/NH3 scrubber and regeneration columns for coke oven gas purification - Hao-Jen Pan; Ming-Chun Fang; Jeffrey D. Ward; Hao-Yeh Lee; Hsun-Yu Lin; Cheng-Ting Hsieh; Chih-Lung Lee; Tzu-Hsien Huang; Yu-Chen Hsieh; Shih-Chieh Lin; Wei-Ti Chou (Journal of Cleaner Production, 2023)

Vibrio salinus sp. nov., a marine nitrogen-fixing bacterium isolated from the lagoon sediment of an islet inside an atoll in the western Pacific Ocean - Wei-Sheng Huang; Li-Ting Wang; Jwo-Sheng Chen; Yen-Ting Chen; Sean Ting-Shyang Wei; Yin-Ru Chiang; Pei-Ling Wang; Tzong-Huei Lee; Shih-Ting Lin; Lina Huang; Wung Yang Shieh (Antonie van Leeuwenhoek, 2022)

Dapagliflozin protects against doxorubicin-induced cardiotoxicity by restoring STAT3 - Wei-Ting Chang; Jhih-Yuan Shih; Yu-Wen Lin; Zhih-Cherng Chen; Wei-Chih Kan; Tsung-Hsien Lin; Chon-Seng Hong (Archives of Toxicology, 2022)

Streptococcus vulneris sp. nov., isolated from wound of patient with diabetic foot ulcer (DFU) - Jen-hao Chung; Li-Ting Wang; Yi-Sheng Chen; Yun-Shien Lee; Shih-Ting Lin; Yu-Chung Chang; Hui-Chung Wu; Yu-Jie Dai; Wei-Qi Liao; Fan-Ching Kao; Jui-hsiang Li (Archives of Microbiology, 2022)

Lactobacillus plantarum PS128 Promotes Intestinal Motility, Mucin Production, and Serotonin Signaling in Mice - Chih-Ming Chen; Chien-Chen Wu; Chin-Lin Huang; Min-Yu Chang; Shih-Hsuan Cheng; Ching-Ting Lin; Ying-Chieh Tsai (Probiotics and Antimicrobial Proteins, 2022)
Lactobacillus plantarum PS128 has been reported as a psychobiotic to improve mental health through the gut–brain axis in experimental animal models. To explore its mechanism of action in the gut, this study aimed to analyze the effects of L. plantarum PS128 ingestion on naïve and loperamide (Lop)-induced constipation mice. We found that, in the two mouse models, the weight, number, and water content of feces in the L. plantarum PS128 group were higher than those in the vehicle control group. Histological observation revealed that L. plantarum PS128 increased the level of colonic mucins including the major mucin MUC2. In addition, the charcoal meal test showed that L. plantarum PS128 significantly increased the small intestine transit in naïve mice, but not in the Lop-treated mice. Since intestinal serotonin has been found to modulate motility, we further analyzed the expression of genes related to serotonin signal transduction in the small intestine of naïve mice. The results showed that L. plantarum PS128 significantly altered the expression levels of Tph1 , Chga , Slc6a4 , and Htr4 , but did not affect the expression levels of Tph2 , Htr3a , and Maoa . Furthermore, immunohistochemistry revealed that L. plantarum PS128 significantly increased the number of serotonin-containing intestinal cells in mice. Taken together, our results suggest that L. plantarum PS128 could promote intestinal motility, mucin production, and serotonin signal transduction, leading to a laxative effect in mice.

Exploiting Sentinel-1 data and machine learning–based random forest for collectively mapping rice fields in Taiwan - Nguyen-Thanh Son; Chi-Farn Chen; Cheng-Ru Chen; Youg-Sin Cheng; Piero Toscano; Chein-Hui Syu; Horng-Yuh Guo; Shu-Ling Chen; Tsang-Sen Liu; Yi-Ting Zhang; Huan-Sheng Lin; Shih-Hsiang Chen; et al. (Applied Geomatics, 2022)

Realization of Natural Human Motion on a 3D Biped Robot For Studying the Exoskeleton Effective - Chi-Ying Lee; Shih Chieh Lan; Jung-Ji Lin; Yu-Ting Lin; Po-Shen Chiang; Wei-Li Hsu; Kuo-Kuang Jen; Andy Y. S. Huang; Jia-Yush Yen (Journal of Medical and Biological Engineering, 2021)

Timing and magnitude of climatic extremes differentially elevate mortality but enhance recovery in a fish population - Ming‐Chih Chiu; Shih‐Hsun Chang; Yu‐Ting Yen; Lin‐Yan Liao; Hsing‐Juh Lin (Global Change Biology, 2021)
The countervailing effects of disturbances (e.g., high mortality and enhanced recovery) on population dynamics can occur through demographic processes under rapidly increasing climatic extremes. Across an extreme‐event gradient, we mechanistically demonstrated how dramatic changes in streamflow have affected the population persistence of endangered salmon in monsoonal Taiwan over a three‐decade period. Our modeling indicated that the dynamics of the age‐structured population were attributed to demographic processes, in which extensive mortality was characterized as a function of climatic extremes and vulnerability in the young stage of fish. In the stochastic simulations, we found that the extensive mortality and high proportion of large fish resulted from extreme flooding, which caused high values of postimpact population recovery. Our empirical evidence suggests that the magnitudes and timing of disturbance can explain the population persistence when facing climatic extremes and thereby challenges the understanding of the mechanistic drivers of these countervailing phenomena under changing environmental conditions.

Vibrio nitrifigilis sp. nov., a marine nitrogen-fixing bacterium isolated from the lagoon sediment of an islet inside an atoll - Wei-Sheng Huang; Li-Ting Wang; Jwo-Sheng Chen; Yen-Ting Chen; Sean Ting-Shyang Wei; Yin-Ru Chiang; Pei-Ling Wang; Tzong-Huei Lee; Shih-Ting Lin; Lina Huang; Wung Yang Shieh (Antonie van Leeuwenhoek, 2021)

Dapagliflozin suppresses ER stress and protects doxorubicin-induced cardiotoxicity in breast cancer patients - Wei-Ting Chang; Yu-Wen Lin; Chung-Han Ho; Zhih-Cherng Chen; Ping-Yen Liu; Jhih-Yuan Shih (Archives of Toxicology, 2021)

Correction to: Glaciimonas soli sp. nov., a soil bacterium isolated from the forest of a high elevation mountain - Wei-Sheng Huang; Li-Ting Wang; Jun-Ning Sun; Jwo-Sheng Chen; Ssu-Po Huang; Shih-Ting Lin; Lina Huang; Wung Yang Shieh (Antonie van Leeuwenhoek, 2021)

Correction to: 4-Phenylbutyric acid protects against vasculitic peripheral neuropathy induced by ischaemia–reperfusion through attenuating endoplasmic reticulum stress - Cay‑Huyen Chen; Ping‑Chen Shih; Han‑Yu Lin; Po‑Kai Wang; Po‑Ting Pan; Ching‑Wei Chuang; Ming‑Chang Kao (Inflammopharmacology, 2020)

Overexpression of a multifunctional β-glucosidase gene from thermophilic archaeon Sulfolobus solfataricus in transgenic tobacco could facilitate glucose release and its use as a reporter - Chih-Hao Huang; Tzu-Ling Huang; Yu-Chang Liu; Ting-Chieh Chen; Shih-Ming Lin; Shyh-Yu Shaw; Ching-Chun Chang (Transgenic Research, 2020)

Synergistic effects of pazopanib and hyperthermia against uterine leiomyosarcoma growth mediated by downregulation of histone acetyltransferase 1 - Chiao-Yun Lin; Angel Chao; Ren-Chin Wu; Li-Yu Lee; Shir-Hwa Ueng; Chia-Lung Tsai; Yun-Shien Lee; Meng-Ting Peng; Lan-Yan Yang; Huei-Jean Huang; Hsin-Shih Wang; Chyong-Huey Lai (Journal of Molecular Medicine, 2020)

Glaciimonas soli sp. nov., a soil bacterium isolated from the forest of a high elevation mountain - Wei-Sheng Huang; Li-Ting Wang; Jun-Ning Sun; Jwo-Sheng Chen; Ssu-Po Huang; Shih-Ting Lin; Lina Huang; Wung Yang Shieh (Antonie van Leeuwenhoek, 2020)

Diverse Community Structures in the Neuronal-Level Connectome of the Drosophila Brain - Chi-Tin Shih; Yen-Jen Lin; Cheng-Te Wang; Ting-Yuan Wang; Chih-Chen Chen; Ta-Shun Su; Chung-Chuang Lo; Ann-Shyn Chiang (Neuroinformatics, 2020)

Expression of AHI1 Rescues Amyloidogenic Pathology in Alzheimer’s Disease Model Cells - Lai-Lei Ting; Hsien-Tsung Lu; Shu-Fen Yen; Thi Huong Ngo; Fang-Yu Tu; I-Shih Tsai; Yi-Hua Tsai; Fu-Yen Chang; Xiao-Jiang Li; Shihua Li; Ching-Kuo Lee; Shu-Huei Kao; et al. (Molecular Neurobiology, 2019)

Development of a Direction-Oriented Motion and Short-Sitting and Lying Tai Chi (DOM-SSLTC) Model for Function Recovery in Stroke Patients - Lian-Hui Lee; Hwai-Ting Lin; Nai-Wen Tsai; Yung-Chieh Yen; Cheng-Hsien Lu; Chun-Chung Lui; Hsien-Ming Chung; Kun-Chang Tsai; Shih-Pin Hsu; Huan-Wen Tsui (Journal of Medical and Biological Engineering, 2019)

Mesorhizobium composti sp. nov., isolated from compost - Shih-Yao Lin; Asif Hameed; Yu-Ting Hsieh; Chiu-Chung Young (Antonie van Leeuwenhoek, 2019)

4-Phenylbutyric acid protects against vasculitic peripheral neuropathy induced by ischaemia–reperfusion through attenuating endoplasmic reticulum stress - Cay-Huyen Chen; Ping-Chen Shih; Han-Yu Lin; Po-Kai Wang; Po-Ting Pan; Ching-Wei Chuang; Ming-Chang Kao (Inflammopharmacology, 2019)

Dose Verification for Tumor Motion with Different Treatment Planning Systems: A Dynamic Thorax Phantom Study - Shih-Neng Yang; Chun-Wei Lin; Mu-Bai Chang; Geoffrey G. Zhang; Kuei-Ting Chou; Yu-Rou Chiou; Shung-Shung Sun; Louis Lui; Tsung-Jung Ho; Tzung-Chi Huang (Journal of Medical and Biological Engineering, 2018)

Important Roles of Ring Finger Protein 112 in Embryonic Vascular Development and Brain Functions - Jen-Hui Tsou; Ying-Chen Yang; Ping-Chieh Pao; Hui-Ching Lin; Nai-Kuei Huang; Shih-Ting Lin; Kuei-Sen Hsu; Che-Ming Yeh; Kuen-Haur Lee; Chu-Jen Kuo; De-Ming Yang; Jiann-Her Lin; et al. (Molecular Neurobiology, 2017)

TM-1-1DP exerts protective effect against myocardial ischemia reperfusion injury via AKT-eNOS pathway - Hui-Chun Ku; Shih-Yi Lee; Chi-Hsuan Chen; Yao-Hsing Wang; Chin-Ting Lin; Shoei-Sheng Lee; Ting-Hsuan Li; Ming-Jai Su (Naunyn-Schmiedeberg's Archives of Pharmacology, 2015)

Description of Niveispirillum fermenti gen. nov., sp. nov., isolated from a fermentor in Taiwan, transfer of Azospirillum irakense (1989) as Niveispirillum irakense comb. nov., and reclassification of Azospirillum amazonense (1983) as Nitrospirillum amazonense gen. nov - Shih-Yao Lin; Asif Hameed; Fo-Ting Shen; You-Cheng Liu; Yi-Han Hsu; Mariyam Shahina; Wei-An Lai; Chiu-Chung Young (Antonie van Leeuwenhoek, 2014)

Nanomolar Naloxone Attenuates Neurotoxicity Induced by Oxidative Stress and Survival Motor Neuron Protein Deficiency - Ya-Yun Hsu; Yuh-Jyh Jong; Yu-Ting Lin; Yu-Ting Tseng; Shih-Hsien Hsu; Yi-Ching Lo (Neurotoxicity Research, 2014)

Identification and characterization of the microRNA transcriptome of a moth orchid Phalaenopsis aphrodite - Ya-Ting Chao; Chun-Lin Su; Wen-Han Jean; Wan-Chieh Chen; Yao-Chien Alex Chang; Ming-Che Shih (Plant Molecular Biology, 2014)

Minocycline accelerates hypoxia-inducible factor-1 alpha degradation and inhibits hypoxia-induced neovasculogenesis through prolyl hydroxylase, von Hippel–Lindau-dependent pathway - Ching-Hao Li; Po-Lin Liao; Ya-Ting Yang; Shih-Hsuan Huang; Cheng-Hui Lin; Yu-Wen Cheng; Jaw-Jou Kang (Archives of Toxicology, 2013)

Estimating Pumping Rates and Identifying Potential Recharge Zones for Groundwater Management in Multi-Aquifers System - Hsien-Tsung Lin; Kai-Yuan Ke; Yih-Chi Tan; Shih-Ching Wu; Gao Hsu; Po-Chia Chen; Shi-Ting Fang (Water Resources Management, 2013)

Global transcriptome analysis and identification of a CONSTANS-like gene family in the orchid Erycina pusilla - Ming-Lun Chou; Ming-Che Shih; Ming-Tsair Chan; Shih-Yi Liao; Chen-Tran Hsu; Yao-Ting Haung; Jeremy J. W. Chen; Der-Chih Liao; Fu-Hui Wu; Choun-Sea Lin (Planta, 2013)

Catalog of Erycina pusilla miRNA and categorization of reproductive phase-related miRNAs and their target gene families - Choun-Sea Lin; Jeremy J. W. Chen; Yao-Ting Huang; Chen-Tran Hsu; Hsiang-Chia Lu; Ming-Lun Chou; Li-Chi Chen; Chia-I Ou; Der-Chih Liao; Ysuan-Yu Yeh; Song-Bing Chang; Su-Chen Shen; et al. (Plant Molecular Biology, 2013)

Rapid detection and identification of the free-living nitrogen fixing genus Azospirillum by 16S rRNA-gene-targeted genus-specific primers - Shih-Yao Lin; Fo-Ting Shen; Chiu-Chung Young (Antonie van Leeuwenhoek, 2011)

Compositions and source apportionments of atmospheric aerosol during Asian dust storm and local pollution in central Taiwan - Man-Ting Cheng; Wei-Chun Chou; Chia-Pin Chio; Shih-Chieh Hsu; Yi-Ru Su; Pei-Hsuan Kuo; Ben-Jei Tsuang; Shuen-Hsin Lin; Charles C.-K. Chou (Journal of Atmospheric Chemistry, 2008)

Inhibitory effect of resveratrol on angiotensin II-induced cardiomyocyte hypertrophy - Tzu-Hurng Cheng; Ju-Chi Liu; Heng Lin; Neng-Lang Shih; Yen-Ling Chen; Meng-Ting Huang; Paul Chan; Ching-Feng Cheng; Jin-Jer Chen (Naunyn-Schmiedeberg's Archives of Pharmacology, 2004)